The main themes of the history of the Southern question in Italy - CAIZZI, B. (PSL Quarterly Review, 2014)
The post-war period in Italy has seen a great increase in research comparing the economic and social conditions of the country’s regions. Moreover, vigorous political action has been taken with a view to reducing the contrasts and the different rates of growth that now separate the North from the South. Present day political writings frequently raise the problem of the date to be ascribed to the birth of the “Southern question”, and historical studies have shown a renewed interest in the origin of this widening of the internal gap. The present article reviews the most important writings published over the years immediately following Italy’s political unification up to the twenties, in connection with a problem that is now a hundred years old. JEL: O14, O52